O Modelo Grupo Prático de Deslocamentos em Psicologia e Epistemologia Genéticas e sua Formalização - Marçal, Vicente Eduardo Ribeiro; Tassinari, Ricardo Pereira [UNESP] (My University, 2013)
In this article, we aim to describe and explain what is the model “practical group of displacements”, introduced in 1937 by Piaget’s work La construction du reel chez l’enfant (Neuchâtel, Paris: Delachaux et Niestlé), essential to comprehension of the construction of space. To this end, we introduce the mathematical notation to describe it, we give the meaning of this notation in the child’s behavior and explains the mathematical structure of group underlying the model.

Neste artigo, temos como objetivo descrever e explicar o que é o modelo Grupo Prático de Deslocamentos, introduzido por Piaget em 1937 na obra La construction du réel chez l’enfant (Neuchâtel, Paris: Delachaux et Niestlé), essencial à compreensão da cons-trução da noção de espaço. Para tanto, introduzimos a notação matemática para des-crevê-lo, damos o significado dessa notação em termos dos comportamentos da criança e explicitamos a estrutura matemática de grupo subjacente ao modelo.
The Model “Practical Group of Displacements” in Genetics Psychology and Epistemology and its Formalization